The relationship between calibrated and actual field seed rates of the external fluted wheel seed metering device with the use of wide level disk harrow - A. Yousif, Lotfie (Gezira Journal of Agricultural Science, 2022)
a field experiment was conducted, at Gedarif University Research Farm, for two consecutive seasons (2006/07 and 2007/08). The objectives of the experiment were to determine the accuracy of external fluted wheel seed metering devices for seeding crops by determining the relationship between the calibrated and actual seed rates for different crops. A wide level disk seeder box equipped with seed metering devices of the external fluted wheel type was used. Five crops of different seed sizes were tested. The calibrated seed rate was determined, using the conventional method when the machine was motionless, and the actual seed rate was determined by using cloth bags to receive seeds when the machine was in motion. The results revealed that actual seed rates were significantly lower than calibrated seed rates for all tested crops. The actual seed rate was 95%, 88%, 96%, 95% and 85% of the calibrated seed rate for sorghum, millet, sesame, sunflower and cotton, respectively. High linear correlations (R 2 = 0.99) between the actual seed rate (dependent variable) and calibrated seed rate (independent variable) were found for all tested seeds. These findings are of considerable importance to farmers and engineers, who use the wide level disk with such type of seed metering devices, to substitute for the reduction in the seed rate in the field.     نفذت تجربة حقلية بالمزرعة التجريبية لجامعة القضارف على مدى موسمين متتاليين (2006/07 و2007/08). هدفت التجربة لتحديد مدى دقة جهاز تلقيم البذور ذو العجلة المموجة الخارجية لزراعة المحاصيل من خلال إيجاد العلاقة بين معدلي البذار المعاير والفعلي لمحاصيل مختلفة. أستخدم المحراث القرصي العريض المزود بصندوق بذور و به أجهزة تلقيم بذور من النوع ذو العجلة المموجة الخارجية. اختبرت خمسة محاصيل ذات بذور بأحجام مختلفة.  تم تحديد معدل البذار المعاير باستخدام الطريقة التقليدية عندما تكون الآلة في وضع توقف وتم تحديد معدل البذار الفعلي باستخدام أكياس من القماش لاستقبال البذور عند ما كانت الآلة في وضع الحركة. أوضحت النتائج أن معدل البذار الفعلي أقل معنويا من معدل البذار المعاير لكل المحاصيل المختبرة. و بلغ معدل البذار الفعلي 95% و 88% و 96% و 95.2% و 85% من معدل البذار المعاير لمحاصيل  الذرة الرفيعة، الدخن، السمسم، زهرة الشمس والقطن على التوالي. كان هنالك معدلات ارتباط خطية عالية (R 2 = 0.99) بين معدل البذار الفعلي (المتغير التابع) ومعدل البذار المعاير (المتغير المستقل) لكل البذور المختبرة. هذه النتائج ذات أهمية كبيرة للمزارعين والمهندسين، الذين يستخدمون هذا النوع من أجهزة تلقيم البذور مع المحراث القرصي العريض، عند تحديد معدلات البذار المطلوبة بطريقة صحيحة.